National integration in vision school: towards '1 Malaysia'? - Ruslan, Norbaiduri; Othman, Azam; Sheikh Ahmad, Ismail (2009)
This paper reports preliminary findings of a larger study of the assessments of intercultural communication in selected Vision schools across Malaysia. The main question is to what extent does Vision Schools foster racial interaction among students of different ethnic groups? Since its establishment, there are 13 schools involved in Vision school concept, however only one Vision School in Subang Jaya, truly delivers the ideal state of having three national school/types, to agree to co-exist in one school compound. The rest of Vision school complexes around Malaysia partially involved national and national-type schools. In those cases, Chinese-type national schools were understood to be reluctant to join the Vision school concept. It is imperative given this observation that the main philosophy behind the establishment of Vision schools be revisited and evaluated by investigating whether the school becomes a platform for pupils and teachers of different ethnic groups to engage in effective intercultural communication. The mission of Vision schools is seen as on par with the current national agenda of „1 Malaysia‟, coined by the Prime Minister of Malaysia, which calls for the three major races in Malaysia to be united and project themselves as being one, rather than as being different. In that respect, the establishment of the Vision schools remains significant and fits with the current national agenda which is to further enhance national integration, in the hope to reach the state of „1 Malaysia‟ in various aspects of life, including in the educational system.